2006
DOI: 10.1358/mf.2006.28.4.990202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral administration of some herbal extracts on food consumption and blood glucose levels in normal and streptozotocin-treated diabetic rats

Abstract: Previous studies in our laboratories suggest that oral administration of some herbal extracts reduce blood glucose concentrations in rats, possibly by interfering with food consumption and/or gastrointestinal absorption of food. Accordingly, we monitored the amounts of food consumed and body weights in separate groups of nondiabetic and streptozotocin-treated diabetic rats, orally treated with some plant extracts (20 mg 100 g -1 body weight) daily for 5 weeks. Control animals were administered the vehicle, cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…These results suggest that LP extracts may alleviate typical T2D symptoms. In previous studies, the antidiabetes mechanisms of natural plant medicines were found to be involved in the maintenance of glucose homeostasis, gastrointestinal glucose absorption, insulinotropic actions, and promoting pancreatic β-cell regeneration [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that LP extracts may alleviate typical T2D symptoms. In previous studies, the antidiabetes mechanisms of natural plant medicines were found to be involved in the maintenance of glucose homeostasis, gastrointestinal glucose absorption, insulinotropic actions, and promoting pancreatic β-cell regeneration [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The plant is known to possess anti-inflammatory (Lansky et al 2008), antihyperglycemic (Musabayane et al 2006) and antioxidant (Palasuwan et al 2005) activities. The literature survey revealed that there are limited scientific studies carried out regarding antinociceptive activity on the bark of Ficus bengalensis to substantiate their therapeutic claim.…”
Section: Ficus Bengalensis Linn (Banyan Tree)mentioning
confidence: 99%
“…Some of the herbal ingredients of MNSO, such as, gymnema (Gholap and Kar, 2004 ), allium (Musabayane et al, 2006), elutherococcus (Yeh et al, 2003), milk thistle (Velussi et al, 1997;Huseini et al, 2006) and ocimum (Hannan et al, 2006;Gupta et al, 2006) are known to facilitate hypoglycemia in diabetics with no apparent effect on normal subjects. Based on the concentrations used, these ingredients probably serve as powerful antioxidants and insulin regulators rather than hypoglycemics, and maintain natural metabolomics of the liver and pancreas.…”
Section: Effect Of Mnso On Liver Histopathologymentioning
confidence: 99%